Penerapan Digitalisasi Catatan Keuangan dan Pemasaran Pada Omah Djadjan Ponpes As-Salafiyah - Riskin Hidayat; Fajar Sodiq (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta (BPJP - STEI), 2022)
MSME Omah Djadjan is one of the MSMEs in Jeruk Village, Pancur District, Rembang Regency with the production of dry and wet cakes. The problems faced by MSMEs Omah Djadjan are that they do not have good financial records either manually or digitally and online marketing only uses Instagram and WhatsApp social media. The proposed solutions to overcome these problems are: 1) Conduct business management training, especially financial management and marketing management; 2) Facilitating manual and digital financial records and marketing in the marketplace; and 3) Provide business assistance. From these solutions, business management training has been realized, especially financial management and digital marketing. The results of the community service program that have been achieved are partners have financial records both manual and digital and online marketing at Shopee